DAMPAK MICROTRANSACTION GAME ONLINE TERHADAP PENGELOLAAN KEUANGAN PRIBADI GENERASI Z DI INDONESIA - Putra, Bagas; Simamora, Virgo; Pravitasari, Endyastuti (JOURNAL OF BUSINESS STUDIES, 2023)
Online games have become entertainment for almost all groups, especially young people who fall into the Generation Z category. Technological developments are also a factor in why online games are also developing. The online game industry has made many innovations, one of which is presenting a microtransaction business model in the games they make. Microtransaction requires a certain amount of real money to buy a number of virtual items. This research aims to analyze the significant impact of microtransactions on financial management, the frequency and nominal value of online game microtransactions as well as how to reduce the negative impacts arising from online game microtransactions on generation Z. The research uses quantitative research methods.Finding the sample was carried out randomly by distributing online questionnaires and sample selection using the Lemeshow formula. Data analysis and processing using SmartPLS-3 resulted in the result that there is a fairly strong impact of online game microtransactions on generation Z's personal financial management.